Two Pseudopolymorphic Star‐Shaped Tetranuclear Co3+ Compounds with Disulfide Anions Exhibiting Two Different Connection Modes and Promising Photocatalytic Properties. Issue 39 (13th August 2015) - Pienack, Nicole; Lühmann, Henning; Djamil, John; Permien, Stefan; Näther, Christian; Haumann, Sebastian; Weihrich, Richard; Bensch, Wolfgang
Abstract The compound [Co4(C6H14N2)4(μ4‐S2)2(μ2‐S2)4] (I) and the pseudo‐polymorph [Co4(C6H14N2)4(μ4‐S2)2(μ2‐S2)4]⋅4 H2O (II) were obtained under solvothermal conditions (C6H14N2=trans‐1, 2‐diaminocyclohexane). The structures feature S22− ions exhibiting two different coordination modes. Terminal S22− entities join two Co3+ centres in a μ2 fashion, whereas the central S22− groups connect four Co3+ cations in a μ4‐ coordination mode. Compound II can be transformed into compound I by heat and storage over P2O5 and storing compound I in humid air yields in the formation of compound II. The intermolecular interactions investigated through Hirshfeld surface analysis reveal that besides S⋅⋅⋅H bonding close contacts are associated with relatively weak H⋅⋅⋅H interactions. A detailed DFT analysis of the bonding situation explains the long SS bonds in the μ4‐bridging S22− units and the short bonds for the S22− moieties in the μ2‐connecting mode. Photocatalytic hydrogen evolution experiments demonstrate the potential of compound II as catalyst.